State-of-the-Art Review on the Analytic Hierarchy Process with Benefits, Opportunities, Costs, and Risks - Petrillo, Antonella; Salomon, Valerio Antonio Pamplona [UNESP]; Tramarico, Claudemir Leif [UNESP] (MDPI, 2023)
The benefits, opportunities, costs, and risks (BOCR) model is a multiple-criteria decision-making (MCDM) model used to elicit a mutually exclusive and collectively exhaustive set of criteria. As an acronym proposed in the theory of the analytic hierarchy process (AHP), the BOCR model has received attention from users of this MCDM method. A state-of-the-art review, an approach to a literature review that is more comprehensive than a rapid review but not as exhaustive as a systematic literature review, was performed with the Scopus database. The overwhelming majority of documents found on BOCR were practical applications, but they were from diverse areas, including business, computer science, and engineering. It is proposed that two main kinds of contributions for future research on BOCR should be methodological and practical.
Keywords: AHP; BOCR; literature review; MCDM